Design and performance test of a modular readout electronic for the kinetic inductance detectors for the COSMO experiment based on commercial components - Conenna, Giulia; Limonta, Andrea; Meinardi, Stefano; Passerini, Andrea; Coppi, Gabriele; Gervasi, Massimo; Nati, Federico; Zannoni, Mario; Albano, Lorenzo; Battistelli, Elia S.; Bersanelli, Marco; Boussaha, Faouzi M.; et al. (Millimeter, Submillimeter, and Far-Infrared Detectors and Instrumentation for Astronomy XII, 2024)
COSMO (COSmic Monopole Observer) is an experiment aimed at the searching for spectral distortions in the CMB (Cosmic Microwave Background) between 120 and 300 GHz. COSMO will be operated from Concordia Station on the Antarctic plateau. The experiment is based on a cryogenic Martin-Puplett interferometer whose superconductive detectors are KIDs (Kinetic Inductance Detectors). The interferometer produces interferograms proportional to the difference between the sky and an internal reference black body. The sky signal has a fast modulation to compensate for the atmospheric fluctuations. A key requirement of the readout is an ultra-fast rate to track the signal modulation and also for detector diagnostic. The readout architecture is based on an IQ transceiver generating a comb of test tones tuned to each detector. We developed a modular readout based on commercial components for reliability and fast prototyping. We were able to reach and sustain a readout rate higher than 60 kHz for 18 detectors. In this contribution a general description of the architecture, together with the main performances in terms of amplitude and phase noise are given.